2017
DOI: 10.1016/j.placenta.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The expression level of C19MC miRNAs in early pregnancy and in response to viral infection

Abstract: Introduction We have previously shown that miRNAs produced from the Chromosome 19 MiRNA Cluster (C19MC), which are expressed almost exclusively in primate trophoblasts and are released into the maternal circulation, reduce viral replication in non-placental cells and can modulate migratory behavior of extravillous trophoblast. We sought to define the expression pattern of C19MC miRNA in early pregnancy and in response to viral infection in vitro and in vivo. Methods We prospectively followed women undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Exposure of PPF or HUtMEC cells to PHT- or BeWo-derived sEVs led to a marked increase in intracellular miR-517a ( Figure 1d ). Importantly, exposure to PHT- or BeWo-derived sEVs attenuated the level of transduced vesicular stomatitis virus (VSV) in the recipient cells ( Figure 1e ), as we have previously shown [ 32 35 , 54 ], thus validating the functionality of the trophoblastic sEVs.
Figure 1.
…”
Section: Resultssupporting
confidence: 80%
“…Exposure of PPF or HUtMEC cells to PHT- or BeWo-derived sEVs led to a marked increase in intracellular miR-517a ( Figure 1d ). Importantly, exposure to PHT- or BeWo-derived sEVs attenuated the level of transduced vesicular stomatitis virus (VSV) in the recipient cells ( Figure 1e ), as we have previously shown [ 32 35 , 54 ], thus validating the functionality of the trophoblastic sEVs.
Figure 1.
…”
Section: Resultssupporting
confidence: 80%
“…Both clusters are imprinted, with C19MC miRNAs expressed solely from the paternal chromosome, and C14MC miRNA expressed solely from the maternal chromosome [7]. The C19MC miRNAs are expressed almost exclusively within trophoblasts, and are exported into the maternal circulation [8] where they can be detected as early as 2 weeks after implantation [9]. They are also detected in the maternal and newborn circulation after delivery [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one study showed that the expression of C19MC miRNAs in pNK cells were significantly upregulated in the third trimester compared with the first‐trimester, and the rapid clearance of C19MC miRNAs from the pNK cells occurred after delivery . This suggests that C19MC miRNA regulates migratory and invasive behaviors of extravillous trophoblasts and plays a role in the establishment of the maternal–fetal interface . In several studies, aberrant levels of pregnancy‐associated placental miRNAs on C19MC in maternal plasma were detected in complicated pregnancies (e.g.…”
Section: Discussionmentioning
confidence: 99%